KARAKTERISTIK ENGINE MOUNTING PADA TEMPERATUR AUSTENISASI TERHADAP SIFAT MEKANIS DAN STRUKTUR MIKRO - Garth Raditya; Erwin Siahaan; Abrar Riza (Jurnal Ilmiah Teknik Mesin POROS, 2021)
Engine mounting is one of the car component which is has optimize function to obtain thesystem in the car is extremely perfect. The engine mounting has to be have behavior ductile by strongestenough to support the car engine whether in rest and moving position. To obtain car engine mountingwhich has these function it has to be treated by treatment. The method was used by using Heat TreatmentSystem which we were Hardening and Tempering. Heat treatment of engine mounting is needed toanalyze the microstructure and mechanical properties of low carbon steel used. Tests carried out attemperatures of 800oC, 850oC, 900oC and normal conditions without heat treatment. Then continued withimpact charpy testing, vickers hardness testing, microstructure observation using microscope and SEM.The tests are carried out in accordance with ASTM E23, ASTM E92, ASTM A370 standards. The Vickerstest results provide the lowest HV value of 118.7Hv at 900oC, while the normal condition is at 137.409Hv.The charpy impact test results give the lowest value of 0.06 j / mm2 under normal conditions, while at900oC at 0.0962 j / mm2. The results with microscopy and SEM, the greater the temperature given to heattreatment, the less pearlite will be, while the amount of ferrite and austenite increases which makes theengine mounting more toughness.